The effects of venlafaxine on depressive-like behaviors and gut microbiome in cuprizone-treated mice - Du, Chunhai; Zhang, Tian; Feng, Chong; Sun, Qian; Chen, ZhiGuo; Shen, Xin; Liu, Ying; Dai, Gengwu; Zhang, Xuan; Tang, Nailong (Frontiers in Psychiatry, 2024)
Background Cuprizone (CPZ)-treated mice show significant demyelination, altered gut microbiome, and depressive-like behaviors. However, the effects of venlafaxine (Ven) on the gut microbiome and depressive-like behavior of CPZ-treated mice are largely unclear. Methods Male C57BL/6J mice were fed a chow containing 0.2% cuprizone (w/w) for 5 weeks to induce a model of demyelination. Meanwhile, the gut microbiota and depressive-like behaviors were assessed after the mice were fed with Ven (20 mg/kg/day) or equal volumes of distilled water for 2 weeks by oral gavage from the third week onward during CPZ treatment. Results CPZ treatment decreased the sucrose preference rate in the sucrose preference test and increased the immobility time in the tail-suspension test, and it also induced an abnormality in β-diversity and changes in microbial composition. Ven alleviated the depressive-like behavior and regulated the composition of the gut microbiota, such as the increase of Lactobacillus and Bifidobacterium in CPZ-treated mice. Conclusion The anti-depressant effects of Ven might be related to the regulation of gut microbiota in the CPZ-treated mice.